Intraoperative neuromonitoring in thyroid surgery: Is the two-staged thyroidectomy justified?. (May 2017) - Calò, Pietro Giorgio; Medas, Fabio; Conzo, Giovanni; Podda, Francesco; Canu, Gian Luigi; Gambardella, Claudio; Pisano, Giuseppe; Erdas, Enrico; Nicolosi, Angelo
Abstract: Background: The aim of this study was to evaluate the diagnostic accuracy of intraoperative neuromonitoring (IONM) in predicting postoperative nerve function during thyroid surgery and its consequent ability to assist the surgeon in intraoperative decision making. Materials and methods: A total of 2365 consecutive patients were submitted to thyroidectomy by the same surgical team. Group A included 1356 patients (2712 nerves at risk) in whom IONM was utilized, and Group B included 1009 patients (2018 nerves at risk) in whom IONM was not utilized. Results: In Group A, loss of signal (LOS) was observed in 37 patients; there were 29 true positive, 1317 true negative, 8 false positive, and 2 false negative cases. Accuracy was 99.3%, positive predictive value was 78.4%, negative predictive value was 99.8%, sensitivity was 93.6%, and specificity was 99.4%. A total of 29 (2.1%) cases of unilateral paralysis were observed, 23 (1.7%) of which were transient and 6 (0.4%) of which were permanent. Bilateral palsy was observed in two (0.1%) cases requiring a tracheostomy. In Group A, 31 (2.3%) injuries were observed, 25 (1.8%) of which were transient and 6 (0.4%) of which were permanent. In Group B, 26 (2.6%) unilateral paralysis cases were observed, 20 (2%) of which were transient and 6 (0.6%) of which were permanent; bilateral palsy was observed in 2 (0.2%) cases. In Group B, 28 (2.8%) injuries were observed, 21 (2.1%) of which were transient and 7 (0.7%) of which were permanent. Differences between the two groups were not statistically significant. Conclusions: Our results show that IONM has a very high sensitivity and negative predictive value, but also good specificity and positive predictive value. For these reasons, in selected patients with LOS, the surgical strategy should be reconsidered. However, patients need to be informed preoperatively about potential strategy changes during the planned bilateral surgery. Future larger and multicenter studies are needed to confirm the benefits of this therapeutic strategy. Highlights: Intraoperative neuromonitoring is safe, effective, and highly predictive. Two-staged thyroidectomy remains a topic of discussion in the surgical field. According to the neuromonitoring results, the surgical strategy should be reconsidered in patients with loss of signal. It is essential to inform the patient preoperatively about potential changes that could be applied to the surgical strategy.